2020
DOI: 10.1016/j.radcr.2020.09.036
|View full text |Cite
|
Sign up to set email alerts
|

Late-onset pneumothorax in a COVID-19 patient treated with ventilation and ECMO: A case report and literature review

Abstract: Coronavirus disease 2019 (COVID-19) has become a major threat to public health since the outbreak in Wuhan in 2019. Chest computed tomography is recommended for COVID-19 cases for evaluation and follow up of pneumonia and related complication. We report the case of a 66-year-old man with underlying hypertension and a history of smoking 76 packs a year; he was frequently monitored by computed tomography for pulmonary changes during the period from early symptom onset to death. Furthermore, he developed a pneumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…16 Multiple studies indicated that PNX usually develops at a relatively late stage (3-8 weeks) after the onset of symptoms. 45,46 In a study by Capaccione et al, the time from intubation to PNX event was 14.9 days which is similar to that described by Belletti et al, in which the time from intubation to PNX was 14 days. 15,28 Most patients who developed PBT in our study died (88%).…”
supporting
confidence: 75%
“…16 Multiple studies indicated that PNX usually develops at a relatively late stage (3-8 weeks) after the onset of symptoms. 45,46 In a study by Capaccione et al, the time from intubation to PNX event was 14.9 days which is similar to that described by Belletti et al, in which the time from intubation to PNX was 14 days. 15,28 Most patients who developed PBT in our study died (88%).…”
supporting
confidence: 75%
“…The mean time for diagnosis of pneumothorax was 11.63 days. Some studies have reported the presence of pneumothorax at the time of first contact with healthcare facility 7 13 while others have reported its development as late as 56 days 14 from the onset of symptoms ( Table 1 and Fig. 4 ).…”
Section: R Esultsmentioning
confidence: 99%
“…Frequency of lung imaging abnormalities per different evaluation setting. References [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ] are cited in the Supplementary Materials…”
mentioning
confidence: 99%